Analisis Mutu Fisikokimia dan Organoleptik Panna Cotta Cincau Hijau (Cyclea barbata Miers) - Louissa Calista Liu; Fadjar Kurnia Hartati; Retnani Rahmiati (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to analyze the effect of green grass jelly leaf extract addition on the physicochemical and organoleptic properties of panna cotta. The research employed a laboratory experimental method using a Completely Randomized Design (CRD) with one factor, namely the combination of green grass jelly leaf extract and UHT milk concentrations at four treatment levels: P1 (20% green grass jelly leaf extract and 50% UHT milk), P2 (25% and 45%), P3 (30% and 40%), and P4 (35% and 35%). The evaluated parameters included Texture Profile Analysis (TPA), protein content, pectin content, and organoleptic assessment covering color, aroma, taste, and mouthfeel. The effectiveness test results indicated that treatment P1 produced the best overall quality with a Result Value (RV) of 0.55562. This treatment was characterized by balanced textural properties, protein content of 5.66%, pectin content of 8.92%, and good panelist acceptance, particularly in taste and mouthfeel attributes. In conclusion, green grass jelly leaf extract has strong potential as a natural gelling agent in panna cotta production, especially at a concentration of 20%, offering a practical local-based alternative to gelatin.